Connecting Purpose and Performance: Rethinking the Purpose of Maintenance of Certification - Harman, Ann E; Warner, David O; Cole, Daniel J (Journal of the American Board of Family Medicine, 2020)
American Boards of Medical Specialties have emphasized single point in time testing for summative assessment of cognitive expertise necessary for board certification. In 2016, the American Board of Anesthesiology introduced Maintenance of Certification in Anesthesiology (MOCA), a longitudinal assessment platform that provides diplomates formative feedback with continuous questions over time and adapts questions to areas of knowledge weaknesses over time. This paper describes the rationale, history, and early results of the American Board of Anesthesiology MOCA platform.American Boards of Medical Specialties have emphasized single point in time testing for summative assessment of cognitive expertise necessary for board certification. In 2016, the American Board of Anesthesiology introduced Maintenance of Certification in Anesthesiology (MOCA), a longitudinal assessment platform that provides diplomates formative feedback with continuous questions over time and adapts questions to areas of knowledge weaknesses over time. This paper describes the rationale, history, and early results of the American Board of Anesthesiology MOCA platform.